Organizational Project Management in Omsk Region Companies: Current State and Development Constraints - Katunina, Irina Vladimirovna (Economy of Regions, 2018)
Despite widespread concept of project management, companies in major regions of Russia are still at the initial level of project management maturity. The paper is aimed to determine the current state and dynamics of organizational project management in the companies of the Omsk region, identify problem areas, and seek directions for further development. The author interviewed managers and project management practitioners in 148 companies from a variety of industries in the Omsk region. The study compares the survey results received during two years (2015-2016). The findings indicate that within the majority of companies, the organizational project management is not fully adopted. The author has empirically tested that high-performers are more likely to appreciate the value of project management than low-performers. However, the only small proportion of companies demonstrates a high level of project management maturity. Moreover, no strong relationship has been found between matured project management processes in a company and its performance. The author revealed and ranged the main problems in the organizational project management development. These problems are concerned with a poor support of organizational enablers. The organizational project management development should be considered in the context of strategic governance and management. The findings contribute to the understanding of key processes, which constitute project capabilities in a company. The research results can be used for building a conceptual model and studying organizational project management dynamics in a region during a longer period.